Let's Discover Our Seashores, Singapore! : Exploring the amazing creatures found on our seashores, with one of Singapore's foremost marine biologists! - Chou, Loke Ming; Chou, Diana; Ong, Eliz (Singapore : WS Education, 2022)
Hello, little readers! Did you know that seashores are full of life and wonder? We can encounter fascinating discoveries unexpectedly, if we keep our eyes open as we walk along the beach.In this full-colour book, through an exciting combination of photography and illustration, Professor Emeritus Chou Loke Ming and co-author, preschool educator Diana Chou, will share marvellous facts about the amazing wonders of creation at the seashores. They will tell you why it is important to protect these precious organisms.So, are you ready to start? Let's Discover Our Seashores, Singapore!
with Videos for Experiential Learning-- Cover pages.
Keywords: Seashore biology -- Singapore -- Juvenile literature; Seashore ecology -- Singapore -- Juvenile literature